2021
DOI: 10.37506/ijfmt.v15i2.14718
|View full text |Cite
|
Sign up to set email alerts
|

E-learning Challenges in Nursing Education during COVID-19 Pandemic-A Narrative Review.

Abstract: Background:The COVID-19 pandemic has alarmed an urgent change in all spectra on the lives of people including education sector. Objective: This narrative review summarizes the challenges of online education in nursing and explores the possible opportunities to improve or maintain the standards of nursing education. Methods: A comprehensive literature search was done to identify the challenges of online education in nursing. Seven primary studies meeting the inclusion criteria, published from the onset of COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…One interesting conclusion from other studies was that online education could enhance theoretical learning. Still, hands-on learning remained irreplaceable for practical nursing skills and could not be substituted by online methods (Divya K Y & Binil V, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One interesting conclusion from other studies was that online education could enhance theoretical learning. Still, hands-on learning remained irreplaceable for practical nursing skills and could not be substituted by online methods (Divya K Y & Binil V, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that the success of e-learning also depended on adequate internet connectivity. Issues like electricity problems and lack of computer literacy still needed to improve for effective online learning (Divya K Y & Binil V, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although e-learning paves the way for students to access the educational environment and materials with their peers during the pandemic, the fact that the use of this technology, in providing online communication, requires features such as internet access and technological infrastructure has brought many challenges especially for students (Divya & Binil, 2021;Kutah, 2021;Suliman et al, 2021). In nursing education, e-learning success has been reported to be associated with the adequacy of available resources and the ability of both students and educators to use information and communication tools (Harerimana & Mtshali, 2021;Divya & Binil, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although e-learning paves the way for students to access the educational environment and materials with their peers during the pandemic, the fact that the use of this technology, in providing online communication, requires features such as internet access and technological infrastructure has brought many challenges especially for students (Divya & Binil, 2021;Kutah, 2021;Suliman et al, 2021). In nursing education, e-learning success has been reported to be associated with the adequacy of available resources and the ability of both students and educators to use information and communication tools (Harerimana & Mtshali, 2021;Divya & Binil, 2021). However, the results of both international (Gharehbagh, Seifi & Moeini, 2021;Kutah, 2021;Subedi, Nayaju, Subedi, Shah, & Mathias, 2020;Suliman et al, 2021;Thapa et al, 2021;Yekefallah, Namdar, Panahi & Dehghankar, 2021) and national (Eren, Korkmaz, Yildirim & Avci, 2021;Terke & Yamac, 2021) studies indicated that infrastructure and technology-related issues constitute a significant part of the negative experiences encountered in the e-learning process.…”
Section: Discussionmentioning
confidence: 99%
“…To date, researchers have synthesised evidence on the impact of COVID-19 on the mental health, well-being, and coping strategies of nursing students (Barrett & Twycross, 2022;Keskin & Özkan, 2021;Majrashi et al, 2021). Other systematic reviews reported the efficacy of blended learning (Jowsey et al, 2020), challenges in online learning (Divya & Binil, 2021), and perceptions of e-learning (Alosta & Khalaf, 2021). While these reviews sufficiently document students' interaction with specific technology and the impact of COVID-19 in general, to our knowledge, no study has synthesised innovations deployed by nursing education in response to the pandemic.…”
Section: Introductionmentioning
confidence: 99%